Becoming Muhammad Ali : A Novel - Patterson, James 1947-; Alexander, Kwame; Anyabwile, Dawud, 1965- (New York : Jimmy Patterson Books/Little, Brown and Company, 2020)
"Before he was a household name, Cassius Clay was a kid with struggles like any other. Kwame Alexander and James Patterson join forces to ... [imagine] his life up to age seventeen in both prose and verse, including his childhood friends, struggles in school, the racism he faced, and his discovery of boxing"--Publisher marketing.
Includes bibliographical references (pages 307-308).
Keywords: Ali, Muhammad, -- 1942-2016 -- Juvenile fiction -- Childhood and youth; Ali, Muhammad, -- 1942-2016 -- Fiction; Boxers (Sports) -- Juvenile fiction; African American boxers -- Juvenile fiction; Boxers (Sports) -- Fiction; African American boxers -- Fiction; Novels in verse